Factors influencing the career choice of accountancy students in Singapore. - Kwok, Ping Ping. (2008)
The purpose of this study is to investigate the factors influencing the career choices of accountancy students in Singapore. Such factors include financial remuneration, work environment, prior exposure, other influences, availability of employment and advancement opportunities and beliefs. Tests were also conducted to investigate the differences in responses between genders, years of study and also students with and without prior exposure.